Comparative efficacy of various methods of physical treatment given to a selected group of patients presented with non specific low back pain - Ullah, Md Ahsan; Rahman, Md Shahidur; Shakoor, MA; Ahmed, Syed Mozaffor; Hasan, Suzon Al (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: low back pain; short wave diathermy; exercise doi: 10.3329/jcmcta.v18i1.3815 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):15-18